2021
DOI: 10.3390/foods10081914
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Morus alba L. and Aronia melanocarpa in a High-Fat Diet-Induced Obese C57BL/6J Mouse Model

Abstract: The present study investigated the synergic effect of extracts of Morus alba (MA) and Aronia melanocarpa (Michx.) (AR) against high-fat diet induced obesity. Four-week-old male C57BL/6J mice were randomly divided into five groups that were fed for 14 weeks with a normal diet (ND), high-fat diet (HD), HD with M. alba 400 mg/kg body weight (MA), HD with A. melanocarpa 400 mg/kg body weight (AR), or HD with a mixture (1:1, v/v) of M. alba and A. melanocarpa (400 mg/kg) (MA + AR). Treatment with MA, AR, and MA + A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Recently, it was proved that phenolic compounds and phenolic extracts might contribute to reducing obesity and dyslipidemia by exerting different mechanisms. The main reported pathways of anti-obesity and dyslipidemic effects involving phenols are (i) enhancement of the in vivo antioxidant defense allowing protection of lipoprotein against oxidation and minimizing hepatic injury [ 13 , 14 ], (ii) inhibition of the key enzymes involved in carbohydrate (such as α-amylase) and fat metabolism (such as pancreatic lipase) which hamper the digestion and absorption of carbohydrates and fats in the small intestine [ 10 , 11 ], and (iii) decreasing of lipogenic adipogenic activities in liver and adipose tissues [ 1 , 9 , 44 , 69 ]. It was reported that gingerol [ 11 ] and betula utilis bark extract [ 10 ] induce the reduction of the absorption of fat and cholesterol by inhibiting the activity of pancreatic lipase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was proved that phenolic compounds and phenolic extracts might contribute to reducing obesity and dyslipidemia by exerting different mechanisms. The main reported pathways of anti-obesity and dyslipidemic effects involving phenols are (i) enhancement of the in vivo antioxidant defense allowing protection of lipoprotein against oxidation and minimizing hepatic injury [ 13 , 14 ], (ii) inhibition of the key enzymes involved in carbohydrate (such as α-amylase) and fat metabolism (such as pancreatic lipase) which hamper the digestion and absorption of carbohydrates and fats in the small intestine [ 10 , 11 ], and (iii) decreasing of lipogenic adipogenic activities in liver and adipose tissues [ 1 , 9 , 44 , 69 ]. It was reported that gingerol [ 11 ] and betula utilis bark extract [ 10 ] induce the reduction of the absorption of fat and cholesterol by inhibiting the activity of pancreatic lipase.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of obesity has proven hugely resistant to therapy, with anti-obesity medications which often showed insufficient efficacy, dubious safety and gastrointestinal side effects (nausea, diarrhea, vomiting, and constipation) [ 8 ]. Natural anti-obesity products (biomolecules, plant crude extracts, mixture of fruit or plant crude extracts) were reported to be an excellent alternative strategy for developing effective and safe anti-obesity and anti-dyslipidemic agents [ 1 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. For example, it was shown that long-term Huangshan Maofeng green extract supplementation remarkably reduced excessive fat accumulation, increased gut microbiota diversity, restored the relative abundance of the microbiota responsible for producing short-chain fatty acids and reduced hyperlipidemia and hepatic steatosis in rats [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PPAR‐γ promotes the expression of C/EBPα, and they (PPAR‐γ and C/EBPα) jointly induce adipocyte differentiation and lipid deposition (Choi et al, 2014). Studies have shown that, compared to normal body type, obese people have higher expression levels of FAS, C/EBPα, SREBP‐1c, and PPAR‐γ expression, and low levels of leptin expression (Kim et al, 2021). Similar results were obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity can be reduced by inhibiting angiogenesis, which subsequently reduces adipogenesis. Several studies have demonstrated the anti-obesity effect of other rice cultivars and herbal medicines ( Ho et al, 2012 ; Lim et al, 2016 ; Kim et al, 2019 ; Kim et al, 2021 ). Anthocyanin-enriched rice berry extract inhibits adipocyte formation and proliferation, and reduces the adipocyte numbers, while resulting in triglyceride accumulation in preadipocytes (3T3-L1 cells) ( Kongthitilerd et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%